ChemInform Abstract: Copper‐Catalyzed Arylation of Nitrogen Heterocycles from Anilines under Ligand‐Free Conditions. Issue 17 (April 2015) - Toummini, Dounia; Tlili, Anis; Berges, Julien; Ouazzani, Fouad; Taillefer, Marc
Abstract Pyrazoles are arylated by anilines via diazotation, in the presence of catalytic amounts of copper(II) acetate.